The extent to which the Islamic studies curricula content has been achieved for the primary stage (higher grades) of the integrative curriculum principles from the teachers of Islamic studies point of view - Al-Mahabi, Ali Mohamed Ahmed (Journal of Educational and Psychological Sciences, 2023)
The research aimed to identify the principles and foundations of the integrative approach, and to know the extent to which the content of the Islamic studies curricula for the primary stage (higher grades (1444)) has achieved these principles and foundations, and whether there are statistically significant differences between the average responses of the sample members attributable to the grade (four, five and six). The descriptive approach is used to achieve the research objectives. It required preparing a list of the integrative approach principles and foundations, which in its initial form consisted of twenty-five paragraphs that was presented to the arbitrators to ensure its validity and suitability and was amended to twenty-one belonging to the integrative approach. A questionnaire according to these principles and foundations was prepared to identify the extent to which the Islamic studies curricula for the primary stage achieve the principles of the integrative approach and was applied to a sample of (50) male/female teachers of Islamic studies in Al-Qunfudhah Governorate. The research results were that the principles and foundations of the integrative approach are largely achieved in the curricula of Islamic studies for the primary stage (higher grades) with a general average (2. 756), The results also indicated that there were no statistically significant differences at the level (05. 0) between the average ranks of the sample members’ responses on the total score to determine the extent to which the content of the Islamic studies curricula for the primary stage (higher grades) achieved the principles of the integrative approach due to the grade variable (four, five and six). The researcher recommended preparing and developing the content of Islamic studies curricula for the primary stage in the light of the integrative approach, and introducing teachers and learners to the importance of this type. Also, strengthening the positive attitude of supervisors and teachers in the primary stage towards it.